2012
DOI: 10.1159/000330791
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of GDF5 through an Adenovirus Vector Stimulates Osteogenesis of Human Mesenchymal Stem Cells in vitro and in vivo

Abstract: The use of stem cells combined with gene therapy could be an important way to facilitate bone regeneration. In this study, the aim was to investigate the potential of growth and differentiation factor-5 (GDF5) to genetically manipulate human mesenchymal stem cells (hMSCs) for bone regeneration. Recombinant adenovirus Ad-GDF5 and Ad-GFP were constructed and identified, and the titer of both were determined. Third-passage hMSCs were infected with adenovirus, and the expression of GDF5 was confirmed by detection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 67 publications
3
11
0
Order By: Relevance
“…GDF-5 was proved to stimulate osteogenic differentiation by enhancing both ALP activity and mineral formation in vitro. 18,51 Also, relative study showed that the gene expressions of Runx2 and OCN were enhanced by GDF-5 addition in a dosedependent manner. 52 Our results are in accordance with these studies, indicating that GDF-5 may have a positive role in osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…GDF-5 was proved to stimulate osteogenic differentiation by enhancing both ALP activity and mineral formation in vitro. 18,51 Also, relative study showed that the gene expressions of Runx2 and OCN were enhanced by GDF-5 addition in a dosedependent manner. 52 Our results are in accordance with these studies, indicating that GDF-5 may have a positive role in osteogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with targeted overexpression of GDF5 in cartilage have a reduced chondrocyte proliferative zone and expanded pre-hypertrophic and hypertrophic zones of the growth plate with increased expression of differentiation markers Ihh and Col10a1 (Tsumaki et al 1999). Overexpression of human GDF5 in human mesenchymal stem cells enhances chondrocyte differentiation and hypertrophy (Coleman et al 2013), induces tenogenic differentiation (Tan et al 2012) and stimulates osteogenesis and bone formation (Cheng et al 2012). GDF5 plays an important role in postnatal joint homeostasis and repair (Luyten 1997), and injection of recombinant human GDF5 into the nucleus pulposus of rabbits after anular puncture of the intervertebral discs is reported to have a reparative effect Chujo et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Cell Source Transplantation Therapeutic Gene Animal Model Ryu CH et al 64) Bone marrow-derived MSCs (human) Xenogenic IFN-β EAE Cobo M et al 60) Adipose-derived MSCs (mice) Allogenic VIP EAE Payne NL et al 65) Adipose-derived MSCs (human) Xenogenic IL-10 EAE Payne NL et al 66) Adipose-derived MSCs (human) Xenogenic IL-4 EAE Mohajeri M et al 67) Bone marrow-derived MSCs (human) Xenogenic FOXP3 EAE Lu Z et al 68) Unknown (human) Xenogenic CNTF EAE Table 1 Gene-Cell Therapy approaches for the treatment of experimental autoimmune encephalomyelitis (EAE) using GM-MSCs tion myocardial repair 41,42) , cartilage repair [43][44][45] and osteogenesis 46) .…”
Section: Authorsmentioning
confidence: 99%